2013
DOI: 10.1111/vde.12002
|View full text |Cite
|
Sign up to set email alerts
|

Pemphigus vulgaris in a Welsh pony stallion: case report and demonstration of antidesmoglein autoantibodies

Abstract: Pemphigus vulgaris is rarely diagnosed in equids. We describe a case that was substantiated by the demonstration of anti-Dsg3 IgG. Response to treatment was poor, with the best response to high doses of prednisolone. Equine pemphigus vulgaris is likely to carry a poor prognosis and if there is no response to treatment, humane euthanasia is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…The time frame for both these two cases appears to be too long to suggest a direct causal association, especially as in both cases laminitis occurred over a week after the onset of clinical signs of systemic disease. In the remaining case, laminitis was reported to have occurred within 4 months of commencing corticosteroid treatment (Winfield et al 2013 In conclusion, no studies that sought to investigate a potential causal association between therapeutic corticosteroid administration and laminitis were identified and there is currently insufficient evidence to support such an association in healthy adult horses. There is weak evidence of an association between administration of multiple doses of systemic corticosteroid and the onset of laminitis in adult horses with underlying endocrine disorders or severe systemic disease.…”
Section: Appraisal Application and Reflectionmentioning
confidence: 96%
“…The time frame for both these two cases appears to be too long to suggest a direct causal association, especially as in both cases laminitis occurred over a week after the onset of clinical signs of systemic disease. In the remaining case, laminitis was reported to have occurred within 4 months of commencing corticosteroid treatment (Winfield et al 2013 In conclusion, no studies that sought to investigate a potential causal association between therapeutic corticosteroid administration and laminitis were identified and there is currently insufficient evidence to support such an association in healthy adult horses. There is weak evidence of an association between administration of multiple doses of systemic corticosteroid and the onset of laminitis in adult horses with underlying endocrine disorders or severe systemic disease.…”
Section: Appraisal Application and Reflectionmentioning
confidence: 96%
“…Despite their frequent use in equine practice, reports of laminitis following the use of prednisolone or dexamethasone are limited to case reports [13,14]. Given their medium-to long-term use, a higher incidence of laminitis would be expected compared with a single administration of triamcinolone.…”
Section: Introductionmentioning
confidence: 99%
“…Given their medium-to long-term use, a higher incidence of laminitis would be expected compared with a single administration of triamcinolone. Despite their frequent use in equine practice, reports of laminitis following the use of prednisolone or dexamethasone are limited to case reports [13,14]. An oral preparation of prednisolone has been recently licensed in the UK and the use of oral glucocorticoids in equine practice is likely to increase as a result.…”
Section: Introductionmentioning
confidence: 99%
“…Equine PV was first anecdotally reported in 2000 [ 30 ], and this was followed by several mentions in textbooks [ 31 ]. To date, there is only one detailed case report of equine PV in a Welsh pony stallion [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…We reported the presence of circulating anti-keratinocyte IgG AA using equine lip as substrate in the only single report of equine PV [ 31 ]. Immunoblotting and immunoprecipitation confirmed that this horse’s AA recognized the extracellular domains of both canine DSG3 and DSG1 [ 31 ]. Whether these AA would recognize also equine DSG3 and DSG1 is logical to expect, but it is not proven.…”
Section: Introductionmentioning
confidence: 99%